Seizure expression, behavior, and brain morphology differences in colonies of Genetic Absence Epilepsy Rats from Strasbourg. Issue 12 (6th November 2014) - Powell, Kim L.; Tang, Howard; Ng, Caroline; Guillemain, Isabelle; Dieuset, Gabriel; Dezsi, Gabi; Çarçak, Nihan; Onat, Filiz; Martin, Benoît; O'Brien, Terence J.; Depaulis, Antoine; Jones, Nigel C.
Summary Objective Originally derived from a Wistar rat strain, a proportion of which displayed spontaneous absence‐type seizures, Genetic Absence Epilepsy Rats from Strasbourg (GAERS) represent the most widely utilized animal model of genetic generalized epilepsy. Here we compare the seizure, behavioral, and brain morphometric characteristics of four main GAERS colonies that are being actively studied internationally: two from Melbourne (MELB and STRAS‐MELB), one from Grenoble (GREN), and one from Istanbul (ISTAN). Methods Electroencephalography (EEG) recordings, behavioral examinations, and structural magnetic resonance imaging (MRI) studies were conducted on GAERS and Non‐Epileptic Control (NEC) rats to assess and compare the following: (1) characteristics of spike‐and‐wave discharges, (2) anxiety‐like and depressive‐like behaviors, and (3) MRI brain morphology of regions of interest. Results Seizure characteristics varied between the colonies, with MELB GAERS exhibiting the least severe epilepsy phenotype with respect to seizure frequency, and GREN GAERS exhibiting four times more seizures than MELB. MELB and STRAS‐MELB colonies both displayed consistent anxiety and depressive‐like behaviors relative to NEC. MELB and GREN GAERS showed similar changes in brain morphology, including increased whole brain volume and increased somatosensory cortical width. A previously identified mutation in the Cacna1h gene controlling the CaV3.2 T‐type calcium channel (R1584P) was present in all four GAERS colonies, but absent in all NEC rats. Significance This study demonstrates differences in epilepsy severity between GAERS colonies that were derived from the same original colony in Strasbourg. This multi‐institute study highlights the potential impact of environmental conditions and/or genetic drift on the severity of epileptic and behavioral phenotypes in rodent models of epilepsy.